Brief Theory-based Intervention to Improve Physical Activity in Men with Psychosis and Obesity: A Feasibility Study - Ahmed Jérôme Romain; Réginald Cadet; Aurélie Baillot (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2020)
Introduction: Physical activity (PA) is recommended to improve physical health in people with psychosis, however, most of them are inactive. Objectives: The objectives of the study were to assess the feasibility of a four-week brief theory-based intervention to improve PA in men with psychosis and obesity. Methods: A Quasi- experimental pre- post design evaluating the feasibility, the participation, and the intervention drop-out rate was conducted. PA, sedentary time, motivational processes of change, and anthropometric measures were evaluated. Results: A total of 38 men with psychotic disorders were approached and 32% participated (n = 12). Among these 12 participants, 75% had schizophrenia, their mean age was 33.2 ± 10.2, and mean Body Mass Index: 35.8 ± 7.7 kg/m2. Besides, all 12 participants (100%) completed the intervention. Participants reported a high satisfaction rate in the intervention. Following the intervention, PA level was increased with a moderate effect size. Similarly, an increase in behavioral processes of change was observed with a moderate effect size. Discussion and conclusion: Hence, the brief theory-based intervention was feasible and could probably improve the PA level in men with psychosis and obesity.